Uji Daya Hasil beberapa Varietas Padi (Oryza Sativa L.) dalam Pot pada Ukuran Media Tanam yang Berbeda - Siti Zainab; Azizah Haryantini; Artadi Artadi; Agung Widya Wardhana; Wawan Apzani (Biofarm Jurnal Ilmiah Pertanian, 2022)
Rice is a staple food that is generally consumed by mostly Indonesian people. However, in 2020 the productivity of rice plants in Indonesia has decreased. This study aims to determine the effect of yield and production of several varieties of rice grown in various sizes of planting media/pots other than in rice fields. This study was arranged according to a completely randomized design (CRD) with two factors (the first factor was size of planting media/pot, while the second factor was type of rice varieties). There were 3 types size of planting media used, i.e 40x40 cm, 50x50 cm and 60x60cm, while the types of lowland rice varieties used wee Ciherang, Inpari 32 and Mekongga. There were 9 treatment combinations in this study. Each treatment was repeated 3 times, so that 27 experimental pots were obtained. The observational data in this study were analyzed using ANOVA (Diversity Analysis) and then further tested with 5% BNJ. The results of the analysis showed that the treatment of pot size was significantly different to the parameters of plant height at the age of 42 to 112 days after planting. The highest results were obtained from the 50 x 50 (cm) pot size treatment, which was 98.88 cm. Out of the treatment of 60 x 60 (cm) planting media, the results were significantly different for the weight parameter of 1000 grains of rice, with the highest achievement value of 25.66 grams. The highest plant growth was obtained from the treatment of 50 x 50 (cm) planting media which was planted with Ciherang variety, which was 99.66 cm. Meanwhile, the highest production was obtained from the treatment of 60 x 60 (cm) planting media planted with the Inpari 32 variety, which was 26.77 grams.